GENE-27. MENINGIOMA RECURRENCE: ROLE OF M1/M2 TUMOUR-ASSOCIATED MACROPHAGE INFILTRATION. (11th November 2019) - Proctor, Dustin; Huang, Jordan; Lama, Sanju; Albakr, Abdulrahman; Van Marle, Guido; Sutherland, Garnette
Abstract: BACKGROUND: Meningioma, a most common brain tumour, has a high rate of recurrence. Tumour-associated macrophages (TAMs) are the most abundant immune cell type in meningioma. TAMs display functional phenotypic diversity and may establish either an inflammatory and anti-tumoural or an immunosuppressive and pro-tumoural microenvironment. TAM subtypes present in meningioma and potential contribution to growth and recurrence is unknown. METHODS: Fluorescence immunohistochemistry was used to evaluate the distribution and quantify M1 and M2 TAM populations in 30 meningioma tissues. Association between quantified M1 and M2 cells and M1/M2 ratio to tumour characteristics including WHO grade, tumour recurrence, size, location, peri-tumoural edema and patient demographics such as age and sex was examined. RESULTS: TAM cells accounted for ~17% of all cells in tumour tissues. Importantly, greater than 80% of infiltrating TAMs were discovered to be of a polarized pro-tumoural M2 phenotype which positively associated with tumour size. TAM subtype profiles differed significantly between non-recurrent (n=18) and recurrent meningioma (n=12) (P=0.044). Specifically, the M1/M2 cell ratio was decreased by ~250% in recurrent tumours. CONCLUSION: This study is the first to confirm existence of pro-tumoural M2 TAMs in the meningioma microenvironment and a potential role in tumour growth and recurrence.